Deposit insurance, discipline market, moral hazard and risk in Banking: A quantitative approach - Feng, Jialun (2009)
The cross-country evidences from two empirical approaches presented in this paper show that explicit deposit insurance scheme reduces market discipline by decreasing capital ratio and required interest rate, while it increases bank’s risk by increasing loan loss reserve and decreasing liquidity ratio. I also use a dataset of deposit insurance design features to examine how different design features e.g. coverage, management affect deposit interest rates and market discipline. Keywords: Deposit insurance; Market discipline; Moral hazard; Bank risks